2014
DOI: 10.1017/s1041610214000416
|View full text |Cite
|
Sign up to set email alerts
|

Review of brief cognitive tests for patients with suspected dementia

Abstract: Background:As the population ages, it is increasingly important to use effective short cognitive tests for suspected dementia. We aimed to review systematically brief cognitive tests for suspected dementia and report on their validation in different settings, to help clinicians choose rapid and appropriate tests.Methods:Electronic search for face-to-face sensitive and specific cognitive tests for people with suspected dementia, taking ≤ 20 minutes, providing quantitative psychometric data.Results:22 tests fitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
142
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(148 citation statements)
references
References 79 publications
3
142
0
3
Order By: Relevance
“…Cognitive screening tools have proven to be simple, useful, and efficient in detecting early cognitive impairment [15,16]. However, the diversity of languages across the world poses a significant barrier in using cognitive screening tools in an effective and efficient manner.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive screening tools have proven to be simple, useful, and efficient in detecting early cognitive impairment [15,16]. However, the diversity of languages across the world poses a significant barrier in using cognitive screening tools in an effective and efficient manner.…”
Section: Introductionmentioning
confidence: 99%
“…The MMSE is used worldwide, primarily for dementia screening (5). The MMSE (total 30 points) measures several cognitive areas, including orientation (10 points), registration (3 points), attention and calculation (5 points), recall (3 points), and language (9 points) (6).…”
Section: Methodsmentioning
confidence: 99%
“…It is a widely used and acceptable measure for people with dementia and is frequently used as a screening tool within memory services. It has been validated against its predecessor the ACE-R and other standardised tests of neuropsychological functioning in early dementia (Hsieh et al 2013), and has been shown to have high internal reliability (Cronbach's α = 0.88 (Velayudhan et al 2014)). …”
Section: Addenbrooke's Cognitive Examination-iiimentioning
confidence: 99%